2020
DOI: 10.1002/jnr.24745
|View full text |Cite
|
Sign up to set email alerts
|

Oral dysfunctions and cognitive impairment/dementia

Abstract: The number of people with dementia is increasing worldwide and is projected to double every 20 years to 74.7 million by 2030 and 131.5 million by 2050. As of 2001, globally, the number of people with dementia aged 60 years or older was estimated to be 24.3 million, and the prevalence of dementia was 3.9%; therefore, approximately 4.6 million new-onset dementia patients will be diagnosed annually (Ferri et al., 2005). Compared with the 2009 report, the prevalence is increasing in Asia and Africa, especially in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 108 publications
2
52
0
Order By: Relevance
“…However, a study has shown that tooth loss reduces the input of periodontal mechanoreceptors from the trigeminal nerve, which affects the hippocampus-dependent cognitive function [ 41 ]. Another study has focused on the effect of the impaired neurotransmission on changes in the trigeminal nervous system-related neural pathways to the hippocampus [ 42 ]. Therefore, it may be important to maintain oral health so that the brain can be stimulated through the periodontal membrane.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study has shown that tooth loss reduces the input of periodontal mechanoreceptors from the trigeminal nerve, which affects the hippocampus-dependent cognitive function [ 41 ]. Another study has focused on the effect of the impaired neurotransmission on changes in the trigeminal nervous system-related neural pathways to the hippocampus [ 42 ]. Therefore, it may be important to maintain oral health so that the brain can be stimulated through the periodontal membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cognitive function, Naruishi, et al, reported that cognitive decline is a risk factor for aspiration pneumonia among elderly hospitalized patients [ 33 ]. Further, patients with declining cognitive function are more likely to have a deteriorating oral environment due to factors such as loss of interest in their own personal appearance, lack of understanding of how to use items, and reduced hand dexterity [ 34 ]. In this study, cognitive function as measured by the MMSE was not associated with aspiration pneumonia, although the participants in the pneumonia group scored lower than those in the non-pneumonia group on the FIM cognitive items of comprehension, representation, and problem solving.…”
Section: Discussionmentioning
confidence: 99%
“…Speech and mastication play fundamental roles in human life; the production of sounds associated with gestures enables communication between subjects, and mastication enables food comminution, bolus formation and nutritional intake. 1,2 These functions can be poor due to advancing age, 2,3 and systemic diseases and buccal alterations, such as xerostomia and tooth loss, can make communication and mastication even more difficult for elderly people. 2,[4][5][6] Thus, fully edentulous elderly people are amongst those experiencing the most negative effects on speech and mastication.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…1,2 These functions can be poor due to advancing age, 2,3 and systemic diseases and buccal alterations, such as xerostomia and tooth loss, can make communication and mastication even more difficult for elderly people. 2,[4][5][6] Thus, fully edentulous elderly people are amongst those experiencing the most negative effects on speech and mastication.…”
Section: Backg Rou N Dmentioning
confidence: 99%